2020
DOI: 10.14202/ijoh.2020.34-40
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of antibiotics as a source of emerging antibiotic resistance: Knowledge, attitudes, and practices of medical staff in the Dassa-Glazoué and Savalou-Bantè's health zones (Benin, West Africa)

Abstract: Background and Aim: Antibiotics have been some great effective molecules against infections since their discovery. The excessive use and misuse of antibiotics have resulted in a selection of antibiotic-resistant strains. Among the reasons involved, the prescription of antibiotics can be important. The present study aimed to contribute to the reduction of antibiotic resistance due to the misuse of antibiotics. Materials and Methods: A knowledge, attitude, and practice survey of health professionals from Savalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Our review findings therefore corroborate what was previously noted in a scoping review which documented global knowledge gaps on AMR in human health including in AMR burden and drivers as well as awareness and education, and with the African region leading the gap chart [98]. Even in studies where AMR knowledge levels were reported to be high among human healthcare professionals, high proportions neither know the extent of AMR nor its effect that AMR could lead to treatment failure [11,12]. In addition, some HCWs neither saw AMR as a problem in their local HCF nor appreciated its impact on their daily routine practice, with such knowledge dearth even documented among physicians in tertiary HCFs [15,37,43], with attendant serious consequences on healthcare cost and patient outcomes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our review findings therefore corroborate what was previously noted in a scoping review which documented global knowledge gaps on AMR in human health including in AMR burden and drivers as well as awareness and education, and with the African region leading the gap chart [98]. Even in studies where AMR knowledge levels were reported to be high among human healthcare professionals, high proportions neither know the extent of AMR nor its effect that AMR could lead to treatment failure [11,12]. In addition, some HCWs neither saw AMR as a problem in their local HCF nor appreciated its impact on their daily routine practice, with such knowledge dearth even documented among physicians in tertiary HCFs [15,37,43], with attendant serious consequences on healthcare cost and patient outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…The majority of the country surveys were among human healthcare practitioners (32, 34.8%) and undergraduate healthcare students (21, 22.8%). The country surveys also involved general public/community dwellers (11), animal producers/farmers (10), patients (5), veterinary drug retailers and dispensers (4), community drug retailers (2), and veterinarians and veterinary paraprofessionals (2). Three other studies surveyed more than one group of respondents.…”
Section: Resultsmentioning
confidence: 99%
“…These results also support the fact that there is a correlation between the presence of antibiotic and heavy metal resistance genes (Di Cesare et al, 2016). Furthermore, it noted a low presence of bla TEM-1 gene, while it is known that penicillin and cephalosporins are widely used in the country, as indicated by the studies of Dougnon et al (2020). It would therefore be interesting to update the scientific data on the consumption of antibiotic molecules in Benin.…”
Section: Discussionsupporting
confidence: 76%
“…This is particularly crucial when antibiotics are administered to dairy animals as a form of dry cow therapy without identifying the bacteria responsible for the disease and its antimicrobial sensitivity profile. The OIE advises monitoring antibiotic resistance in animals while WHO urges prudent and sensible use of antibiotics in the community as a whole [14].…”
Section: Introductionmentioning
confidence: 99%